Eksistensi Tarian Kabasaran Dalam Perayaan Kuncikan di Kelurahan Buyungon - Tamon, Max Laurens; Tombuku, Tiara Debora; Ramaino, Almen S (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2025)
The involvement of kabasaran dance in kuncikan celebrations in Buyungon Village is an important part that cannot be separated. Kabasaran dance in the celebration of kuncikan as an identity of the Minahasa community that must be preserved, especially in the midst of a very strong modernisation that causes a lack of interest in the younger generation. The purpose of this research is to describe the influence of modernisation on the values of kabasaran dance in kuncikan celebrations and describe the role of the younger generation in preserving kabasaran dance during kuncikan celebrations in Buyungon Village. The research method used in this research is the historical method. The data collection techniques used were interviews, documentation and questionnaires in the form of questions asked to the local government in Buyungon Village, religious leaders and the younger generation. The analysis technique was carried out through the results of interviews, field notes and documentation which were adjusted to the problems studied and then described through words and sentences. The results of this study show that although modernisation brings challenges to the preservation of kabasaran dance. However, the values contained in this dance are still relevant and important to the Buyungon community. Furthermore, the involvement of the younger generation in the preservation of this dance, shows a hope to maintain cultural heritage, with an approach that involves collaboration between various parties, as well as the utilisation of technology and innovation in the preservation process.